Effect of Aerobic Training with Blood Flow Restricting on Static Balance, Lower Extremity Strength, and Thigh Hypertrophy in Females with Multiple Sclerosis - Masumeh Darvishi; Mojdeh Rafiei; Baharak Moradi Kelardeh; Saeed Keshavarz (Islamic Azad University, 2017)
Introduction: Multiple sclerosis (MS) is the most common neurological, progressive and debilitating disease in young adults. The purpose of this study was to investigate the effect of 8-week aerobic training with restricted blood flow on static balance, thigh strength, and thigh hypertrophy in females with MS. Methods: 19 females with MS disease (age= 56.11±7.43 years and BMI= 22.78±1.78 kg.m-2) were selected and divided randomly into four groups: aerobic training (A), blood flow restriction (BFR), combination aerobic training and blood flow restriction (COM), and control group (C). Before and after 8 weeks of aerobic training (45 min aerobic training with 50- 60% HRmax) and restricted blood flow; the balance, thigh strength and hypertrophy were measured. Paired sample t-test, two-way repeated measure ANOVA and Tukey's post hoc test were used to analyze statistical data (p≤0.05). Results: The results showed significant difference between groups in balance (p= 0.02), thigh strength (p= 0.001), and hypertrophy (p= 0.04). Post hoc test showed a significant difference between the COM and C groups (p = 0.003) and COM and BFR groups (p = 0.03); but the COM group didn't have better balance scores than the A (p=0.37) and BFR (p=0.15) groups. Also in thigh strength there was a significant difference between the COM and A group (p = 0.008) and between the COM and C group (p = 0.001); but the COM group didn't have better thigh strength than BFR (p=0.08) group. Also there was a significant difference between COM and C group in hypertrophy (p = 0.02). Conclusion: According to the results aerobic training with blood flow restriction leads to increased balance, strength and thigh hypertrophy in MS patients so this approach can be taken instead of traditional aerobic training to decrease disability in MS patients.